The migration of UK trained GPs to Australia: Does risk attitude matter?. Issue 11 (November 2019) - van der Pol, Marjon; Scott, Anthony; Irvine, Alastair
Highlights: Risk attitude plays a role in migration as these are risky decisions. UK-qualified GPs who migrated to Australia were compared to GPs in Scotland. They have a similar risk attitude towards financial risk. They were more risk averse with regards to career and clinical risk. Migration may be associated with lower career and clinical uncertainty in Australia. Abstract: Background: Little is known about the drivers of migration of GPs. Risk attitude may play an important role as migration is fundamentally a risky decision that balances the risks of staying with the risks associated with leaving. This paper examines the association between risk attitudes and the migration of UK GPs to Australia. Methods: GPs who qualified in the UK but work in Australia and who responded to the Medicine in Australia: Balancing Employment and Life (MABEL) national longitudinal survey of doctors, were compared with GPs based in Scotland who responded to a survey. Risk attitudes were elicited for financial risks, career and professional risks and clinical risks on a scale from 1 to 5. Results: GPs in Scotland and UK trained GPs in Australia have similar risk attitudes for financial risk. However, UK trained GPs in Australia are less willing to take clinical and career risks. Conclusion: GPs who migrated to Australia after qualifying in the UK were more risk averse about their career and clinical risks. This may suggest that more risk averse GPs migrate to Australia due to pull factors such as less uncertainty around career and clinical outcomes in Australia. The uncertain NHS climate may push more risk averse doctors away from the UK.